Soliton solutions to constrained nonlocal integrable nonlinear Schrödinger hierarchies of type (−λ,λ) - Ma, Wen-Xiu (International journal of geometric methods in modern physics, 2023)
The paper aims to generate nonlocal integrable nonlinear Schrödinger hierarchies of type ( − λ , λ ) by imposing two nonlocal matrix restrictions of the AKNS matrix characteristic-value problems of arbitrary order. Based on the explored outspreading of characteristic-values and adjoint characteristic-values, exact soliton solutions are formulated by applying the associated reflectionless generalized Riemann–Hilbert problems, in which characteristic-values and adjoint characteristic-values could have a nonempty intersection. Illustrative models of the resultant mixed-type nonlocal integrable nonlinear Schrödinger equations are presented.